Enhancing individual productivity via the deployment of the office inventory management system. - Binti Nik Othman, Nik Amalin; Mohamad Rosman, Mohamad Rahimi; Alimin, Noor Azreen; San, Lee Yee (International Journal of Accounting, Finance and Business, 2026)
Inventory management is one of the important activities in human resource management (HRM) practices. Inventory management enables accurate decision-making, quick organizational planning, and preparing organization for potential low stock management. However, many organizationsowadays still relies on manual based inventory system due to several reasons, such as lack of expertise, high implementation cost, and lack of urgency. Therefore, this project is devoted to the development of a web-based Office Inventory Management System (OIMS) intended to enhance the efficiency and effectiveness of office inventory management of an organization. The OIMS is developed to allow a centralized system of managing inventory items, updating inventory levels, tracking booking requests, accepting or refusing booking requests and creating well-structured reports. The system development was based on the Waterfall methodology that involves implementation, testing, requirements analysis, system design, and implementation. The system architecture is based on the three layers: presentation layer (HTML, CSS, JavaScript), application layer (PHP), and database layer (MySQL). The outcomes of the functional testing show that the system is functional, and it achieves the set goals.